Efficacy of Lodoxamide Versus Sodium Cromoglycate in Vernal Keratoconjunctivitis (Medical Forum Monthly, 2024)
Objective: To determine efficacy of lodoxamide as compared to that of sodium cromoglycate when used for the treatment of vernal keratoconjunctivitis.Study Design: Prospective comparative clinical trial.Place and Duration of Study: This study was carried out at the Department of Pharmacology and Therapeutics Basic Medical Sciences Institute (BMSI) in collaboration with Department of Ophthalmology Jinnah Postgraduate Medical Center (JPMC) Karachi from April 2010 to October 2010.Materials and Methods: A total of untreated 80 cases with clinical diagnosis of vernal keratoconjunctivitis (VKC) of 5-29 years of age and of both sexes were included in this study. Patients of other types of allergic conjunctivitis and of VKC already on medication were not included in this study. Follow up visits were carried out at fortnightly intervals for the period of at least three (03) months to rule out comparative efficacy of the two drugs.Results: We studied a total of 80 cases, 56 males (70%) and 24 females (30%) with diagnosis of VKC. All cases were divided in two groups; group A and group B. Group A comprised of 40 patients who used lodoxamide whereas; Group B comprised 40 patients who used sodium cromoglycate. No significant difference in demographic features was found in two groups (p>0.05). The results showed significant improvement in all symptoms and signs in 60 days of study in group A (lodoxamide) and in group B (sodium cromoglycate) improvement was observed in 90 days of the study (p<0.05).Conclusion: Improvement in all the symptoms and signs was earlier (within 30 days of study) in group A than in group B.